Penolakan Konsep Ketubuhan Patriarkis di dalam Proses Menjadi Perempuan Melalui Pemikiran Merleau-Ponty dan Simone De Beauvoir - Retno Daru Dewi G.S. Putri (Jurnal Filsafat "WISDOM", 2018)
Descartes’ dualism of mind and body implies relationship of mind and body in the articulation of human thinking. While seemingly reflects both men and women, this concept of dualism has in practice changed due to the existing social construction that differentiate human based on their sex. The ongoing social discrimination against women implies philosophy’s deficiency in addressing human universal issues. In addressing this issue, this research emplyos Merleau-Ponty’s notion of embodied perception and Beauvoir’s conception on ambiguity to argue on the importance of women’s body freedom in understanding the world’s phenomenons around them. The application of these concepts is proposed to provide an independent mode of becoming a woman and to offer a philosophical solution for women’s issues.